From mechanism to therapies in systemic lupus erythematosus. Issue 2 (March 2017) - Paley, Michael A.; Strand, Vibeke; Kim, Alfred H.J.
Abstract : Purpose of review: Systemic lupus erythematosus (SLE) is a disabling and deadly disease. Development of novel therapies for SLE has historically been limited by incomplete understanding of immune dysregulation. Recent advances in lupus pathogenesis, however, have led to the adoption or development of new therapeutics, including the first Food and Drug Administration–approved drug in 50 years. Recent findings: Multiple cytokines (interferon, B lymphocyte stimulator, IL-6, and IL-17), signaling pathways (Bruton's Tyrosine Kinase, Janus kinase/signal transducer and activator of transcription), and immune cells are dysregulated in SLE. In this review, we cover seminal discoveries that demonstrate how this dysregulation is integral to SLE pathogenesis and the novel therapeutics currently under development or in clinical trials. In addition, early work suggests metabolic derangements are another target for disease modification. Finally, molecular profiling has led to improved patient stratification in the heterogeneous SLE population, which may improve clinical trial outcomes and therapeutic selection. Summary: Recent advances in the treatment of SLE have directly resulted from improved understanding of this complicated disease. Rheumatologists may have a variety of novel agents and more precise targeting of select lupus populations in the coming years.